From Surau to Market: Transforming the Economic Values of the Malay Community within the Framework of Religious Moderation - Jamaludin, Jamaludin; Holijah, Holijah (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This article discusses the transformation of economic values within the Malay community, shifting from a collective and spiritual system centered on the surau to an individualistic, market-based economy. Modernization and urbanization have diminished the surau's role as a center for ethics and economic solidarity. Traditional practices such as antar pakatan, once based on mutual cooperation, have turned into wage-based and service-oriented transactions. Using a sociological approach through Marcel Mauss's gift exchange theory, the article highlights how values of reciprocity and social honor are being eroded by market logic. The concept of religious moderation (wasathiyyah) is proposed as a bridge between tradition and modernity. This qualitative library-based study emphasizes the importance of revitalizing the surau as a contextual and inclusive center of Islamic economic values.